KOMPLEKS MAKAM KUNO INOWEEHI II (PAKANDEATE) DI KABUPATEN KONAWE - Aksan Juliantho; Syahrun Syahrun; sandy suseno (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2018)
This study uses the theory of cultural history, the concept of tombs, and Islamic concepts in the Konawe royal community, in helping answerresearch questions. The main data in the study are the remains of the struc-ture of the tomb building, and data supporting or supporting it are artefactual data which are loose findings foundaround the Inoweehi II (Pakandeate) tomb complex. The researcherused field observation techniques, namelysurface surveying and documentation.The results showed that megalithic remains in the form of ancient tombs inthe Inoweehi II (Pakandeate) tomb complex were quite diverse, the number of tombs in this tomb complexnum-bered fourteen tombs with among them five tombs which were still equipped with gravestones. The results of theclassification of the entire tomb have been found three types of tombs, among others, L2LTS (oval gravestone,tier 2, and imperfect tomb circle shape), P-K (flat headstone, no tomb, and square box tomb shape), K-K (squaresquare gravestone, without tombs, and square box tombs). The form of tombs and gravestones in the Inoweehi II tomb complex are the result of acculturation of pre-Islamic and Islamic cultures seen from the shape of the tomband its narratives that use upright stones (menhirs) which are remains of megalithic culture.